Effect of mulberry supplemented diet on growth performance and carcass characteristics of broiler chicks - Simol, Carlina Freddie; Tuen, Andrew Alek; Amartalingum, Rajan (2009)
Feed is the major expense in poultry production and accounted for 60-70% of the total production cost. The trend in Malaysia, over the last few years, has been one of increasing feed cost due to the increase in the cost of raw ingredients. Hence, it is important to find alternative feed ingredients which can be incorporated into poultry diet to reduce cost. Here we report the result of preliminary experiment to study the effect of feeding broiler chicks with a diet supplemented with ground mulberry leaf. The experiment consisted of thirty chicks fed with a diet containing ground mulberry leaf and commercial concentrate (30:70) while 30 others chicks were fed the commercial concentrate only as a control. Based on a 49-day observation period, only a single mortality was recorded for the treatment diet while 8 were recorded for the control. Live weight of chicks fed with the treatment diet ranged from 2.0 to 2.95 kg as compared to 1.5 to 1.8 kg for the control. Feed conversion efficiency was 0.49 and 0.55 for the treatment and control diet, respectively. The carcass characteristics and colour of internal organs were apparently better for the mulberry leaf supplemented diet compared to the control diet. This preliminary investigation showed that broiler production based on diet containing ground mulberry leaf can be an economically viable enterprise.